INTEGRATING E-COMMERCE WEBSITES AND SOCIAL MEDIA TO INCREASE SALES OF ASSIGNMENT WRITING SERVICES - Kevin; Rio Sutrisno; Ayu Lasmi Sitanggang; Agsha Dwi Agustin Ginting; Rana Haura; Harry Pratama Figna (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The development of digital technology has brought significant changes to marketing patterns and strategies across various business sectors, including assignment-making services, which are developing as a form of digital-based entrepreneurship. High levels of competition require businesses to no longer rely on traditional marketing approaches and instead optimize the use of digital media in a smart, targeted, and integrated manner. This study aims to examine the role of smart digital marketing through the use of e-commerce websites and social media in increasing sales of assignment-making services. This research employed a descriptive qualitative approach using a case study method. Data collection involved observing digital marketing activities, interviewing customers, and documenting interactions on social media and websites. The data obtained was systematically analyzed to illustrate the effectiveness of the implemented digital marketing strategy. The research results show that integrating social media as a means of promotion, interaction, and communication with an e-commerce website as a transaction center can increase customer trust, expand market reach, and simplify the service ordering process. A well-planned, consistent, and data-driven digital marketing strategy has been proven to positively contribute to increased sales while supporting the sustainability of assignment-making services in the digital era.